2022
DOI: 10.3390/ijerph19158921
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aircraft Delays on Population Noise Exposure in Airport’s Surroundings

Abstract: The motivation behind this research was to analyse the consequences of aircraft operations’ delays on cumulative noise levels produced upon the neighbouring communities and to estimate the relative change in the number of people annoyed by aircraft noise. Many studies showed that residents’ reactions to abrupt changes in noise exposure were more intense compared to the anticipated ones. Aircraft delays may cause such abrupt changes in noise exposure by increasing the traffic in some periods compared to the sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Padhra [30] captured the data for the single day turnarounds around Europe and showed that time between the APU switched on and the aircraft departing is equal to 15 minutes or more for over half of the flights. This is exceptionally important when considering a probability of delay where Zijadić et al [51] measured that 64 % of arrivals and 46 % of departures were delayed at Sarajevo airport.…”
Section: Internal Combustion Engines Usagementioning
confidence: 99%
“…Padhra [30] captured the data for the single day turnarounds around Europe and showed that time between the APU switched on and the aircraft departing is equal to 15 minutes or more for over half of the flights. This is exceptionally important when considering a probability of delay where Zijadić et al [51] measured that 64 % of arrivals and 46 % of departures were delayed at Sarajevo airport.…”
Section: Internal Combustion Engines Usagementioning
confidence: 99%
“…These maps usually depict cumulative noise metrics, such as L DN (day-night average sound level) or L night (night average sound level) that account for multiple noise events caused by different departing and arriving traffic in a specified timeframe. The downside of this type of depiction is that it lacks in accounting for abrupt and short changes in noise exposure, e.g., caused by delaying maneuvers, such as holdings or procedural turns, which are shown to inflict more negative residents' responses [21]. For the purpose of this study, only singleevent noise metrics were used-SEL (sound exposure level) and L Amax (the maximum A-weighted level of noise recorded by the observer).…”
mentioning
confidence: 99%